2020
DOI: 10.3390/diagnostics10090666
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Digital Single-Operator Cholangioscopy in the Diagnosis of Indeterminate Biliary Strictures by Targeted Biopsies: A Systematic Review and Meta-Analysis

Abstract: Background: Biliary strictures are frequently encountered in clinical practice. The determination of their nature is often difficult. This study aims to systematically evaluate the efficacy and safety of the second generation of digital single-operator cholangioscopy (SpyGlass DS, DSOC) in indeterminate biliary strictures (IBDS) through biopsies. Methods: All relative studies published in Medline, the Cochrane Library, Web of Science, and EMBASE were included. The diagnostic tests for IBDS were compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…However, the accurate visual diagnosis of biliary strictures and assessment of the extent of a lesion are not possible by ERCP, and treatment of bile duct stones by ERCP procedures is sometimes difficult. Peroral cholangioscopy (POCS) has recently become a useful modality for diagnostic and therapeutic procedures in patients with biliary diseases [ 1 , 2 ]. POCS enables direct visualization of the biliary tract and the sampling of suspicious lesions, together with lithotripsy with electrohydraulic lithotripsy (EHL) or laser lithotripsy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accurate visual diagnosis of biliary strictures and assessment of the extent of a lesion are not possible by ERCP, and treatment of bile duct stones by ERCP procedures is sometimes difficult. Peroral cholangioscopy (POCS) has recently become a useful modality for diagnostic and therapeutic procedures in patients with biliary diseases [ 1 , 2 ]. POCS enables direct visualization of the biliary tract and the sampling of suspicious lesions, together with lithotripsy with electrohydraulic lithotripsy (EHL) or laser lithotripsy.…”
Section: Introductionmentioning
confidence: 99%
“…IBS is defined as biliary strictures with aetiologies that cannot be established after standard diagnostic investigations such as laboratory tests, imaging (such as computed tomography or magnetic resonance cholangiopancreatography), or procedures (such as endoscopic retrograde cholangiopancreatography (ERCP)-guided tissue biopsy)[ 40 ]. This section will discuss the role of choledochoscopy in diagnosing IBS, specifically when along with the diagnostic algorithm it should be done, optimal choledochoscope choice, the two main ways choledochoscopy can be used, and factors affecting its diagnostic accuracy.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Direct visualization by choledochoscopy permits the identification of mucosal features suspicious for malignancy and targeted biopsies. In a recent meta-analysis by Wen et al [ 40 ] involving 356 patients across 11 studies, the visual impression was more sensitive than choledochoscopy-guided biopsy across DSOC, FSOC, and D-POC (95% vs 74%, 84.5% vs 60.1%, 83%-92% vs 43%-89.5%). However, specificity was higher in choledochoscopy-guided biopsy than visual impression across DSOC, FSOC and D-POC (98% vs 92%, 98% vs 82.6%, 97% vs 84%-92%)[ 40 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The diagnostic accuracy of D-SOC is further improved by D-SOC-guided biopsy, which allows precise tissue sampling of the detected lesions. In a meta-analysis by Wen et al [ 43 ], SpyBite (Boston Scientific) biopsy showed a pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio of 0.74 (95%CI: 0.67-0.80), 0.98 (95%CI: 0.95-1.00), 10.52 (95%CI: 5.45-20.32), 0.31 (95%CI: 0.23-0.41), and 65.18 (95%CI: 26.79-158.61), with a lower complication rate mainly ERCP-related. Acute cholangitis was the most common complication with a rate of 1.8%[ 43 ].…”
Section: Cholangioscopymentioning
confidence: 99%
“…A point of great debate is the number of biopsies needed to obtain adequate tissue for a diagnostic histopathological assessment. Based on currently available studies, the number of biopsies is not defined with any certainty, but more than two biopsies are required to reach a sensitivity > 70%[ 23 , 43 ]. In a randomized multicenter investigation, an average of six biopsy specimens were taken during POCS, achieving a sensitivity of 68.2%, which increased up to 95.5% if visual impression at cholangioscopy was added to biopsy forceps performance[ 41 ].…”
Section: Cholangioscopymentioning
confidence: 99%